Genetic diversity among commercial arabica coffee (Coffea arabica L.) varieties in Ethiopia using simple sequence repeat markers. Issue 2 (4th March 2021) - Benti, Tadesse; Gebre, Endale; Tesfaye, Kassahun; Berecha, Gezahegn; Lashermes, Philippe; Kyallo, Martina; Kouadio Yao, Nasser
ABSTRACT: Ethiopia is the center of origin and genetic diversity of arabica coffee. Forty-two commercial arabica coffee varieties were developed by Jimma Agricultural Research Center (JARC) of Ethiopian Institute of Agricultural Research (EIAR) and released for production under diverse agro-ecologies of the country. Information on the level of genetic diversity among these varieties is scarce. Out of the 42 varieties, the genetic diversity of 40 widely cultivated commercial varieties was assessed using 14 simple sequence repeat (SSR) markers. These markers revealed polymorphism among the varieties. High average number of polymorphic alleles (7.5) and polymorphic information content (PIC = 80%) per locus were detected among the varieties. The genetic similarity among varieties using the Jaccard's similarity coefficient ranged from 0.14 to 0.78, with a mean of 0.38. The range of genetic similarity coefficient values in 92% of the possible pair-wise combinations varied from 0.14 to 0.50, indicating the presence of distant genetic relatedness among the varieties. Unweighted pair group method using arithmetic mean (UPGMA) clustering showed six major clusters and three singletons. Coffee varieties, belonging to the same geographic origin, were distributed across clusters. This study represents the first evidence of the presence of a high level of genetic diversity in Ethiopian commercial arabica coffee varieties. Divergent varieties with complementing traits could be crossed to develop productive hybrid coffee varieties.